PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN SIKAP TOLERANSI DI SEKOLAH DASAR NEGERI 77 BUTON KECAMATAN LASALIMU SELATAN - Perkasa, Windayani; Sulastri; Abdul Rahim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) teachers in instilling tolerance at SD Negeri 77 Buton, Lasalimu Selatan District. The research employs a qualitative approach with a case study method, allowing researchers to gain an in-depth understanding of teaching practices and social interactions in elementary schools. The findings reveal that PAI teachers play a crucial role in shaping students' tolerance through various teaching methods, such as classroom discussions, reflections on Islamic teachings that emphasize peace, and experience-based approaches. Challenges in implementing tolerance values include students' limited understanding of diversity, an unsupportive social environment, and the lack of educational resources addressing tolerance from an Islamic perspective. To address these challenges, PAI teachers apply innovative strategies such as collaboration with parents and the community, the use of technology in teaching, and extracurricular activities focused on cultural and religious diversity.